Analysis of Risk Factors Associated with Maskne in the Era of the COVID-19 Pandemic - Salsabila Az-Zahra; Nelva Kamilah Jusuf (Sumatera Medical Journal, 2023)
Background: The necessity to always use a mask in the era of the COVID-19 pandemic has given rise to a new term called maskne. Maskne is the appearance of acne that is triggered by wearing a mask. It usually occurs specifically in the area covered by the mask, focused on the cheeks, chin, and nose. Objective: This study aims to determine the risk factors associated with the occurrence of maskne. Methods: A cross-sectional study was conducted on the Faculty of Medicine students, Universitas Sumatera Utara class 2018. This study uses primary data from questionnaires and observation of respondents' face photos. Results: Based on statistical analysis, 99 out of 221 respondents (44.8%) experienced maskne. Bivariate analysis shows p-values <0.05 for gender, duration of mask use, and previous acne history. On the other hand, it was obtained p-value >0.05 for the type of mask and mask changing habit. Conclusion: Based on multivariate analysis, the p-value <0.05 for gender indicates that gender is the most dominant risk factor in the incidence of maskne. Furthermore, there is a significant association between gender and the occurrence of maskne. Females are twice as likely to experience maskne.